Interview with Olga Kolo. Territorial Governance and Place Branding - Damiani, Marco (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
In the present age of globalisation, urban and territorial policies make use – among others – of tools related to the so-called Place Branding practices, in Europe and worldwide. Such a process implies the activation of a complex governance activity addressed to a broad target audience, in order to create (together with all the public, private and third-sector actors active in the territory) an identity or a new identity of places, cities, regions or states, which otherwise risk undergoing a process of homologation and/or political-cultural marginalisation, with very high costs in terms of identity and territorial governance (or poor territorial governance). Place Branding procedures fit into this context to counter the risk of loss of local identity of places subjected to processes of cultural homologation. In particular, Place Branding processes are implemented to try to enhance the authentic characteristics of a place, its history, culture, areas of excellence, the widespread mentality of the people who live there, their lifestyle, the organised forms of widespread sociality. The aim is to build a new and unique territorial 'vision', so that new added value can be created in the places affected by these local governance processes. In this sense, the involvement of citizens becomes fundamental. Citizens are in fact understood as strategic stakeholders to be taken into consideration in order to successfully carry out a successful operation such as that contained in Place Branding processes.